Weed Control in Leafy Vegetables (Lettuce, Endive, Escarole and Spinach) - William M. Stall; Joan A. Dusky (EDIS)
Revised! HS-203, a 4-page fact sheet by William M. Stall and Joan A. Dusky, describes effective weed management practices for leafy vegetables in Florida and provides a table listing herbicides available to growers for chemical weed control. This publication updates the 2003 table to reflect current recommendations. Published by the UF Department of Horticultural Sciences, October 2006.